The square of a binomial \((a - b)^2\) is given by the formula: \[ (a - b)^2 = a^2 - 2ab + b^2 \] In this case, \(a = x\) and \(b = 10\).
Substitute \(a = x\) and \(b = 10\) into the formula: \[ (x - 10)^2 = x^2 - 2(x)(10) + 10^2 \]
Calculate each term:
Combine these results: \[ (x - 10)^2 = x^2 - 20x + 100 \]
\((x - 10)^{2} = \boxed{x^2 - 20x + 100}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.